(untitled) (Nigerian Journal of Technology, 2020)
Following my election as Dean of Engineering on July 08, 2020, I have assumed office on August 1, 2020. I have managed all the editorial works of this journal since 2010 while combining the job as Faculty PG Rep, Director of our Equipment Maintenance and Development Center, Director of Computer Communications Center, Head of my base Department and even as Associate Dean. It has been really tasking over the years but this is a job I accepted with all my heart and I have given it my all.